Right ventricular outflow tract stenting promotes pulmonary artery development in tetralogy of fallot - Guo, Hui; Wu, Zhongshi; Zhao, Tianli; Yang, Jinfu; Hu, Shijun; Huang, Can; Yang, Yifeng; Xie, Li (Frontiers in Surgery, 2023)
Background Right ventricular outflow tract (RVOT) stenting seems to be suggested as a promising treatment option and an alternative to modified Blalock-Taussig shunt (mBTS) in the initial palliation of patients with Fallot-type lesions in recent years. This study sought to assess the effect of RVOT stenting on the growth of the pulmonary artery (PA) in patients with Tetralogy of Fallot (TOF). Methods Retrospective review analyzing 5 patients with Fallot-type congenital heart disease with small pulmonary arteries who underwent palliative with RVOT stenting and 9 patients underwent modified Blalock-Taussig shunt within 9 years period. Differential left PA (LPA) and right PA (RPA) growth was measured by Cardiovascular Computed Tomography Angiography (CTA). Results RVOT stenting improved arterial oxygen saturation from median of 60% (interquartile range [IQR]: 37% to 79%) to 95% (87.5% to 97.5%) (p = 0.028). The LPA diameter Z-score improved from −2.843 (−3.51–2.037) to −0.78 (−2.3305–0.19) (p = 0.03), the RPA diameter Z-score improved from median −2.843 (−3.51–2.037) to −0.477 (−1.1145–0.459) (p = 0.002), the Mc Goon ratio increased from median 1 (0.8–1.105) to 1.32 (1.25–1.98) (p = 0.017). There were no procedural complications and all 5 patients have undergone final repair in the RVOT stent group. In the mBTS group, the LPA diameter Z-score improved from −1.494 (−2.242–0.6135) to −0.396 (−1.488–1.228) (p = 0.15), the RPA diameter Z-score improved from median −1.328 (−2.036–0.838) to 0.088 (−0.486–1.223) (p = 0.007), and there were 5 patients occur different complications and 4 patients was not attained the standards of final surgical repair. Conclusion RVOT stenting, compared with mBTS, seems to better promote pulmonary artery growth, improve arterial oxygen saturations, and have less procedure complications in patients with TOF who being absolute contraindicated for primary repair due to high risks.